9
$\begingroup$

In an induction proof for $\sum_{k = 1}^n \frac{1}{k^2} \leq 2 - \frac{1}{n}$ (for $n \geq 1$), I was required to prove the inequality $\frac{1}{(n+1)^2} + \frac{1}{n+1} < \frac{1}{n}$.

This is my attempt:

$$ \begin{align} \frac{1}{(n+1)^2} + \frac{1}{n+1} &= \frac{1+(n+1)}{(n+1)^2} \\ &=\frac{n+2}{(n+1)^2} \\ &=\frac{n+2}{n^2 + 2n + 1} \\ &<\frac{n+2}{n^2 + 2n} (\text{since } n \geq 1)\\ &=\frac{n+2}{n(n+2)}\\ &=\frac{1}{n} \end{align} $$

I am just wondering if there is a simpler way of doing this.

$\endgroup$
6
  • 3
    $\begingroup$ for $n=1$, the inequality $\sum_{k=1}^n \frac{1}{k^2}<2-\frac{1}{n}$ is not true. it only holds for $n>2$. $\endgroup$
    – Kumar
    Jun 20, 2019 at 1:57
  • $\begingroup$ I think the < should be $\geq$. $\endgroup$
    – 1123581321
    Jun 20, 2019 at 2:11
  • $\begingroup$ No, it's correct. Because as $n\rightarrow \infty$ the inequality approaches $\frac{\pi^2}{6}$. $\endgroup$
    – Kumar
    Jun 20, 2019 at 2:27
  • $\begingroup$ Sorry should be $\leq$ $\endgroup$
    – 1123581321
    Jun 20, 2019 at 2:28
  • 2
    $\begingroup$ Nice variety of solutions. I upvoted then all. $\endgroup$ Jun 20, 2019 at 2:56

5 Answers 5

15
$\begingroup$

To prove the inequality you were required to prove, note

$\dfrac1{n+1}+\dfrac1{(n+1)^2}<\dfrac1{n+1}+\dfrac1{(n+1)^2}+\dfrac1{(n+1)^3}+...=\dfrac{\dfrac1{1+n}}{1-\dfrac1{n+1}}=\dfrac1n$

$\endgroup$
8
$\begingroup$

Instead of comparing $\frac{1}{(n+1)^2} + \frac{1}{n+1}$ and $\frac{1}{n}$, we can compare $\frac{1}{(n+1)^2}$ and $\frac{1}{n}-\frac{1}{n+1}$. Then, what we have is $$\frac{1}{(n+1)^2} = \frac{1}{(n+1)(n+1)} < \frac{1}{n(n+1)}=\frac{1}{n}-\frac{1}{n+1} \implies \frac{1}{(n+1)^2} < \frac{1}{n}-\frac{1}{n+1}$$ $$\implies \frac{1}{(n+1)^2} + \frac{1}{n+1} < \frac{1}{n}$$


Alternatively, by using the same way, we could try to prove $$\frac{1}{n}-\frac{1}{(n+1)^2}-\frac{1}{(n+1)} > 0$$ For this one, we have $$\frac{1}{n}-\frac{1}{(n+1)^2}-\frac{1}{(n+1)} = \frac{(n+1)^2-n-n(n+1)}{n(n+1)^2} = \frac{1}{n(n+1)^2} > 0$$ since $n \ge 1$. Therefore, the result follows.

$\endgroup$
0
7
$\begingroup$

Multiply through by $n(n+1)^2$ (a positive number since $n \ge 1$ ) to get $$n+n(n+1) < (n+1)^2$$ $$n < (n+1)^2 - n(n+1)$$ $$n < (n+1)(n+1-n)$$ $$n < n+1$$ Which is true of course for all $n$; in particular $n\ge 1$

$\endgroup$
2
  • $\begingroup$ I like this answer but I'm looking for something that is simpler / more obvious. $\endgroup$
    – 1123581321
    Jun 20, 2019 at 1:40
  • $\begingroup$ Another method is to use the common fraction of $n(n+1)^2$ and bring everything to one side: the result is similar: $n(n+1)^2 \gt 0$ which for the given conditions is true. $\endgroup$
    – WaveX
    Jun 20, 2019 at 3:25
4
$\begingroup$

Just for the fun of it, you can re-write your inequality as: $$\frac{1}{n}-\frac{1}{n+1}>\frac{1}{(n+1)^2}.$$ This can be re-writen as: $$\int_{n}^{n+1}\frac{1}{x^2}dx>\frac{1}{(n+1)^2},$$ or, if $f(x)=\dfrac{1}{x^2}$: $$\int_{n}^{n+1}f(x)dx>f(n+1),$$ which is obvious if you consider that $f$ is strictly decreasing and positive on $(0,+\infty)$ and that the right-hand side of the inequality is the area of a rectangle with height $f(n+1)$ and a basis of $1$ - see the figure below. enter image description here

$\endgroup$
1
$\begingroup$

Your way is right, but you need to open the sumation from $k=2$: $$\sum_{k=1}^n\frac{1}{k^2}=1+\sum_{k=2}^n\frac{1}{k^2}<1+\sum_{k=2}^n\frac{1}{k(k-1)}=1+\sum_{k=2}^n\left(\frac{1}{k-1}-\frac{1}{k}\right)=2-\frac{1}{n}.$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.